Knowledge, Attitude and Practices Related to Pet Contact and Associated Zoonoses in Jammu - R. Jeelani, R. Nanda, P. Kumar, R. Raina, B. Bhushan, M. Rashid, R. K. Sharma, P. S. Mahapatra; A. W. Ganai (Indian Journal of Extension Education, 2018)
Many zoonotic infections are transmitted through contact with animals including household pets. A pretested questionnaire cum interview schedule was employed to collect the data pertaining to the research problem from a total of randomly selected 248 respondents in order to investigate the objectives of this study which were; pet keeping practices, attitude and knowledge level of pet owners regarding scientifically advocated pet keeping practices. The mean age of pet owners was about 36 years with a standard deviation of 12.47. Majority of the pet owners (91.5%) were male and only (8.5%) were females with a good educational and occupational background. Majority of the respondents kept canines as pets for leisure, fed them commercial feeds and housed them indoors. Children in the families played with pets and pet owners were very concerned about the zoonotic transmissions. Mostly pet owners had a neutral attitude towards pets as a part of their family and the knowledge index regarding scientifically advocated pet practices was only about 45 per cent.